Developing and validating a hierarchical model of external responsiveness: A study on RFID technology - Hossain, M.; Quaddus, Mohammed (Springer, 2014)
Information Systems researchers demonstrate that organizations are very often influenced by external environment; success of an organization and its associated industry is largely dependent on how they respond to the external factors. Although a number of external factors have been explored in literature, still little is known on their degree of impact and hence their relative importance. Therefore, advancing research on organizational external (environmental) responsiveness requires clarifying the theoretical conceptualizations and validating the associated dimensions. After conducting an extensive literature search followed by a qualitative and quantitative study, the current study develops and validates a multi-dimensional hierarchical model of external responsiveness and investigates its effect on adoption intention.The findings of the study show that; in the context of Radio Frequency Identification (RFID) technology, external responsiveness is a third-order, reflective construct which is reflected by external pressure (further is reflected by government pressure, market pressure, mimetic pressure, and normative pressure), external support (reflected by government support, vendor support, and associative support), and external uncertainty (reflected by market and technology uncertainty). Moreover, the impact of the third-order and second-order constructs on the endogenous variable (i.e. intention to adopt RFID) is examined and found to have positive influences. This study is the first reported attempt that categorizes the dimensions of external responsiveness and validates with empirical data. This study concludes with implications and future research directions.